MENULIS KREATIF SEBAGAI MEDIA KRITIK SOSIAL DALAM PUISI “PERINGATAN” KARYA WIJI THUKUL - Al’ Hayati, Zaytun; Fauziah, Amilatul; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to demonstrate that creative writing, particularly in the form of poetry, can serve as a powerful and effective medium for social criticism. The focus of the study is the poem Peringatan (“Warning”) by Wiji Thukul, written in the context of political repression during Indonesia's New Order regime. Using a qualitative descriptive method and a literary social criticism approach, the analysis examines each stanza of the poem, which delivers a sharp warning regarding the imbalanced relationship between the people and those in power. The findings show that the poem reflects creative aspects through its direct diction, symbolism of resistance, and rhetorical structure that poignantly exposes social and political realities. Through this work, Wiji Thukul voices the people’s frustrations against silenced aspirations and authoritarian control. Thus, “Peringatan” becomes a form of creative expression as well as an ideological weapon against structural injustice.